2018
DOI: 10.1016/j.irfa.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure volatility in Europe

Abstract: Contrary to the predictions of the trade-off theory, we find that many companies in Europe had substantial variation in their capital structures between 2006 and 2016. We show that this pattern occurred across countries. Companies with the most volatile debt ratios tended to be smaller, and were less profitable. Their high debt volatility was partly due to high volatility in operating and investing activities, and partly due to a reduced propensity to let cash balances and equity payouts absorb the fluctuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 29 publications
7
35
4
Order By: Relevance
“…In addition, a study by De Angelo and Roll (2015) found that capital structure stability is the action, not the rule. Other than that, the study by Campbell and Rogers (2018) states that firms with a high volatile capital structure tend to gain less profit and lead to stricter dividend policies compared to firms with a stable capital structure. Empirically, prior research finds that a firm's capital structure is influenced not only by firm-specific but also by country-specific factors (Li and Islam, 2019).…”
Section: Determinants Of Capital Structurementioning
confidence: 99%
“…In addition, a study by De Angelo and Roll (2015) found that capital structure stability is the action, not the rule. Other than that, the study by Campbell and Rogers (2018) states that firms with a high volatile capital structure tend to gain less profit and lead to stricter dividend policies compared to firms with a stable capital structure. Empirically, prior research finds that a firm's capital structure is influenced not only by firm-specific but also by country-specific factors (Li and Islam, 2019).…”
Section: Determinants Of Capital Structurementioning
confidence: 99%
“…Nevertheless, Ardalan (2018) proved that there prevails an optimal capital structure for the firm. However, for companies based in the major markets of United Kingdom, Germany, France, and PIIGS (Portugal, Italy, Ireland, Greece, and Spain) significant discrepancy was established in their capital structures between 2006 and 2016 (Campbell and Rogers 2018). As well, DeAngelo and Roll (2015) noticed for U.S. companies, capital structure stability is the exception, not the rule.…”
Section: Introductionmentioning
confidence: 98%
“…Pioneering studies on capital structure based their hypotheses on perfect capital market conditions that lead to rather theoretical assumptions. Campbell and Rogers (2018) discussed about the Corporate Finance Trilemma that occurs since companies would like to decide on their debt, cash holdings, and equity payout policies at the same time, but firms cannot. Nevertheless, Ardalan (2018) proved that there prevails an optimal capital structure for the firm.…”
Section: Introductionmentioning
confidence: 99%
“…The high share of debt volatility most often leads to reduced profitability, and is a consequence of high volatility of operating and investment activities or a tendency to release cash balances and principal payments for absorbing fluctuations (Campbell & Rogers, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%